2019
DOI: 10.1109/comst.2018.2881008
|View full text |Cite
|
Sign up to set email alerts
|

The Sensable City: A Survey on the Deployment and Management for Smart City Monitoring

Abstract: This is the accepted version of a paper published in IEEE Communications Surveys and Tutorials. This paper has been peer-reviewed but does not include the final publisher proofcorrections or journal pagination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
100
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(101 citation statements)
references
References 194 publications
(214 reference statements)
0
100
0
1
Order By: Relevance
“…In smart homes, different motion and door sensors are installed at different locations and the primary objective is to recognize and assess activities but in smart homes, physical activities (i.e., running, cycling) cannot be performed due to the nature of activities.The most widely used sensors for recording physical activities data using a smartphone are the accelerometer, gyroscope, and position sensor [8,[14][15][16][17][18][19][20]]. An accelerometer is capable of tracking activity readings to infer complex user motions, such as tilt, swing, or rotation.Researchers showed that the accelerometer sensor is the most reliable and cheapest alternate of wearable sensors for physical activity recognition [19,[21][22][23]. They showed that the accelerometer can also be used in combination with other sensors such as a gyroscope, light, proximity, barometer, linear acceleration and magnetometer sensor for better activity recognition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In smart homes, different motion and door sensors are installed at different locations and the primary objective is to recognize and assess activities but in smart homes, physical activities (i.e., running, cycling) cannot be performed due to the nature of activities.The most widely used sensors for recording physical activities data using a smartphone are the accelerometer, gyroscope, and position sensor [8,[14][15][16][17][18][19][20]]. An accelerometer is capable of tracking activity readings to infer complex user motions, such as tilt, swing, or rotation.Researchers showed that the accelerometer sensor is the most reliable and cheapest alternate of wearable sensors for physical activity recognition [19,[21][22][23]. They showed that the accelerometer can also be used in combination with other sensors such as a gyroscope, light, proximity, barometer, linear acceleration and magnetometer sensor for better activity recognition.…”
mentioning
confidence: 99%
“…Researchers showed that the accelerometer sensor is the most reliable and cheapest alternate of wearable sensors for physical activity recognition [19,[21][22][23]. They showed that the accelerometer can also be used in combination with other sensors such as a gyroscope, light, proximity, barometer, linear acceleration and magnetometer sensor for better activity recognition.…”
mentioning
confidence: 99%
“…While some attempts at integration has been done in the context of environmental monitoring, involving sensors for temperature, relative humidity, dew point, gas, wind, rain, and atmospheric pressure [49,50], the benefits of integration extend to traffic monitoring, where sensor readings are complemented with contextual data. Traffic monitoring is conducted by sensing capabilities, the GPS receivers installed on modern vehicles and a mixture of air quality sensor and acoustic sensors along the given road [51].…”
Section: Multiple Sensorsmentioning
confidence: 99%
“…The IoT paradigm is also being deployed in several other contexts and applications areas, including different industry sectors [83,84], smart cities [85,86], and healthcare [87,88]. Besides data communication, an IoT system has to perform a multitude of other tasks.…”
Section: Iot Architecturementioning
confidence: 99%